Kandungan Acid Detergent Fiber Dan Neutral detergent Fiber Jerami Jagung fermentasi Dengan Mengunakan Jamur Trichoderma Viride Dengan Lama Inkubasi Berbeda - Natalia Usman; ellen salah (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2019)
The research was aimed at investingating acid detergent fibre neutral detergent Fiber content in corn straw fermented using Trichoderma Viride in different Incubation Time. It applied compeletey Randomizend Design consisting Of 4 treatments and 4 repetitions, hence, it resulted in 16 units of an experiment. The Treatments consisted of corn straw withhout inoculation (control), 7% corn straw Fermented with Trichoderma viride in 1 week incubation time, 7% corn straw Fermented with Trichoderma Viride in 2 weeks incubation time, and 7% corn straw fermented with Trichoderma Viride in 3 weeks incubation time.Analysis of variance result shows that corn straw fermented using Trichoderma Viride in different Incubation Time gave significant inflluance toward ADF content (p0,05). Besides , corn straw fermentd using Trichoderma Viride in different incubation Time gave significant influence toward NDF content(p0,05).